1987
DOI: 10.1128/aem.53.1.47-52.1987
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the spore coat in germination of Bacillus cereus T spores

Abstract: Bacillus cereus T spores were prepared on fortified nutrient agar, and the spore coat and outer membrane were extracted by 0.5% sodium dodecyl sulfate-100 mM dithiothreitol in 0.1 M sodium chloride (SDS-DTT) at pH 10.5 (coat-defective spores). Coat-defective spores in L-alanine plus adenosine germinated slowly and to a lesser extent than spores not treated with SDS-DTT, as determined by decrease in absorbance and release of dipicolinic acid and Ca2. Spores germinated in calcium dipicolinate only after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
1
15
0
2
Order By: Relevance
“…Chemical treatment of the spores. In order to modify the coat, spores of the wild strain were chemically treated by the method described by Aronson and Fitz-James (1) which has subsequently been adopted by others (18,36). Briefly, 50 mg of clean spores were suspended in 50 ml of a freshly prepared solution of 5 mm DTT, 0.5% SDS and 0.1 M NaCl with the pH adjusted to 10.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical treatment of the spores. In order to modify the coat, spores of the wild strain were chemically treated by the method described by Aronson and Fitz-James (1) which has subsequently been adopted by others (18,36). Briefly, 50 mg of clean spores were suspended in 50 ml of a freshly prepared solution of 5 mm DTT, 0.5% SDS and 0.1 M NaCl with the pH adjusted to 10.…”
Section: Methodsmentioning
confidence: 99%
“…There is abundant evidence in the literature that the coats may be involved in spore germination. Spores whose coats are modified by chemical treatments almost invariably show altered or reduced germinability (3,4,6,8,10,18,27,36). Some coatless or coat-defective mutant spores are also deficient in germination (2,5,8,14,17,22).…”
Section: Restoration By Calcium Of L-alanine-induced Germinabilities mentioning
confidence: 99%
See 1 more Smart Citation
“…The proteinaceous coat layers of the bacterial spore (exclusive of the exosporium) are believed to have a protective function and to play some role in germination (Aronson and Fitz-James, 1976;Kutima and Foegeding, 1987). A cryptic cortex lytic enzyme (Brown et al, 1982;Foster and Johnstone, 1987) or proteases involved in the activation of this enzyme (Boschwitz etal., 1985) may be associated with an integral part of the coat.…”
Section: Introductionmentioning
confidence: 99%
“…The SDS-DTT-treated spores seem to be lacking in a significant portion of "functional" Ca2+ necessary for germination (21). Kutima and Foegeding (15) described that some components (Mr, > 12 kDa) located in the spore coat or the outer membrane were extracted by 0.5% SDS-100 mM DTT and were essential for rapid germination of coatdefective spores. Recently, Shyu and Foegeding (24,26) reported that a novel calcium-binding protein (Mr, 24 kDa) was purified from dormant spores of B. cereus T. From these results, it is considered that the SDS-DTT-treatment of B. cereus spores might remove functional Ca2+ and a certain component that specifically binds or traps Ca2+ , .…”
Section: Inhibition By Divalent Metal Cationsmentioning
confidence: 99%